Atypical Presentation of the Classical Form of Locked-In Syndrome in a Young Patient - Ngoda Manongi MD, MS; Jana Clough DO; Ryan Mirchin DO; Kory A. Byrns MD; Steven Tversky DO (SAGE Publishing, 2023)
Locked-in syndrome (LIS) is an uncommon neurologic disorder that manifests in quadriplegia and anarthria with preserved cognition and self-awareness. Generally, patients with LIS may live for years with preserved quality of life and cognitive function, but with severe disability. There are 3 types of LIS: classic, partial, and total. The classical form is defined by total immobility, with preservation of the ability to perform vertical eye movements, blink, and maintain a normal level of consciousness. We present an unusual case of classical LIS in a 54-year-old man who presented initially with acute-onset left lower extremity weakness and dysarthria with radiographic evidence of extensive, acute right paramedian pontine infarction and high-grade vertebral artery stenosis. However, a week later, the patient developed sudden-onset aphonia, bilateral facial palsy, and quadriplegia with repeat magnetic resonance imaging of the brain showing expansion of right paramedian pontine stroke to also involve the left paramedian pons, without significant change to the vertebral stenosis and basilar artery patency.